Role of Indigenous health workers in the delivery of comprehensive primary health care in Canada, Australia, and New Zealand: a scoping review protocol. Issue 11 (14th November 2021) - Violette, Richard; Spinks, Jean; Kelly, Fiona; Wheeler, Amanda
ABSTRACT: Objective: The aim of this review is to identify and describe Indigenous health workers' roles, functions, activities, and involvement in decision-making in the provision of primary health care for Indigenous peoples and communities in Canada, Australia, and New Zealand. Introduction: The Indigenous health worker workforce is the cornerstone to providing culturally safe, primary health care for Indigenous peoples and communities. Yet, wide-ranging role variation has created a general lack of understanding of who Indigenous health workers are, what Indigenous health workers do, and how to best coordinate their roles and skills with other care providers to further improve the health care experience and outcomes for Indigenous peoples and communities. Inclusion criteria: This review will consider full text, peer-reviewed publications and gray literature that include Indigenous health workers who identify as belonging to, and are recognized as such by their communities, any First Peoples group in Canada (First Nations, Inuit, Métis), Australia (Aboriginal, Torres Strait Islander), and New Zealand (Māori); and who describe their role as the provision of primary health care to Indigenous peoples and communities, in clinical and non-clinical settings, in both mainstream health systems and within community-controlled primary health care sectors. Methods: MEDLINE, CINAHL, Scopus, Embase, Informit (Indigenous Collection, New Zealand Collection, Rural and Remote Health Database, APAIS-ATSIS, Aboriginal and Torres Strait Islander health bibliography), Sociological Abstracts, and Australian Indigenous HealthInfoNet will be searched for studies. Additional sources of unpublished literature, including government websites and community-controlled health organization websites in Canada, Australia, and New Zealand, will also be searched. Articles in English and French will be included, with no set date restrictions. Screening and selection will follow JBI methodology and findings will be summarized in tabular form accompanied by narrative text.